(untitled) (Annals of Medical Research, 2021)
Aim: An increase in the elderly population owing to an extended average life expectancy leads to an increase in the geriatric patient admissions to the emergency departments (EDs). The aim of this study was to investigate the intensity of geriatric patients among all admissions to the emergency department and to determine the importance of these patients in hospitalizations from the EDs.Material and Methods: Geriatric patients aged over 65 years were retrospectively evaluated between 1 January 2017and 31 December 2018. The patients were divided into two groups by the age: 65–79 (group I) and ≥80 years (group II). The number of days of hospitalization and mortality in the intensive care units (ICUs) and clinics were examined.Results: Of 386.670 patients aged over 18 years who were admitted to the ED, 17% (n=65.907) were aged ≥65 years. 64.4% of the patients who were hospitalized in the ICU from the ED were aged ≥65 years. The sex distribution of the patients who were admitted to but died in the ED in both the groups was as follows: Of 62.1% (n=72) in Group II were females, and of 62.1% (n=82) in Group I were males.Conclusion: In parallel with the increase in the number of geriatric patients in ED, there is a crowding in both clinics and ICUs. This article highlights the importance of geriatric patients in emergency department admissions and their importance in hospitalizations. Hospitalization and mortality rates increase with age. Keywords: Emergency department; crowding; geriatric patients.